Is bioelectrical impedance spectroscopy accurate in estimating changes in fat-free mass in judo athletes? - Matias, C. N.; Santos, D. A.; Fields, D. A.; Sardinha, L. B.; Silva, A. M. (Journal of Sports Sciences, 2012)
Bioelectrical impedance spectroscopy (BIS) provides an affordable and practical assessment of fat-free mass (FFM). However, little information is available on the assessment of changes in fat-free mass in top-level athletes using BIS. The aim of this study was to examine the accuracy of BIS in tracking changes in fat-free mass of elite male judo athletes from a period of weight stability to just before competition, using the four-compartment model (4C model) as reference method. In total, 27 elite male judo athletes (age 22.2 ± 2.8 years) were evaluated. Measures of body volume assessed by air displacement plethysmography, bone mineral content by dual-energy X-ray absorptiometry, and total-body water assessed with deuterium dilution were used in a 4C model. Fat-free mass was also assessed by BIS (FFMBIS). Changes in FFMBIS were not significantly different from measured by the reference method (P = 0.000). Furthermore, the r 2 was 0.62 and the standard error of the estimate was 1.03 kg. The limits of agreement ranged from -3.36 to 2.59 kg with no bias observed. These findings demonstrate the viability of BIS as a valid tool for tracking fat-free mass in elite male judo athletes. However, based on the wide limits of agreement observed, BIS is less valid at an individual level for tracking fat-free mass in these athletes.